Hookah smoking among young people in Bamako - Diara Abdourahamane (EDP Sciences, 2021)
Introduction: In Mali, shisha has become the most common form of tobacco consumption, which is not without danger for the consumer health. The aim of this study was to assess the consumption level of shisha among young people in the District of Bamako. Methods: This was a prospective study from March 2019 to March 2020. A total of 200 young shisha smokers aged 40 or under were included in this study. Results: The male sex was predominant, with 75% of cases. The majority, or 81.5%, were under the age of 25. According to study data, 26% of respondents said they smoke shisha at least once a day. Over a quarter of cases reported concurrent use of two or more addictive substances. The most common association was with alcohol (13%), cannabis (9%) and cocaine (4.5%). According to the results, 69% of respondents thought that shisha is less harmful than cigarettes. Conclusion: Consumption of shisha has grown considerably in Mali in recent years. This study has highlighted a new form of multiple drug addiction, which could be harmful to the health of consumers. Thus, the authorities concerned must take appropriate measures to combat this scourge.